Church teaching and the views of youth on sexual practices : a study amongst Anglican youth of the Cape Town diocese aged 12-19 - Mash, Rachel (Stellenbosch : University of Stellenbosch, 2011)
Thesis (M. Th.)--University of Stellenbosch, 2006.